ANALISIS ORIENTASI PASAR KEARAH KEUNGGULAN KINERJA RUMAH SAKIT DI KOTA DAN KABUPATEN MALANG - Fariz Fariz (Politeknik Negeri Sriwijaya, 2014)
Health development in indonesia is a business that is very strategic in the improvement of quality of human resource. Based on the essential and strategic health problems existing, that is required the establishment of facilities, a system of management and implementation of adequate at the hospital that a part of national health care system. The problem in this research: are hospital in the city and district of Malang has market oriented that focuses on customers and how can the condition of the performance of hospitals that focuses on competitor customers, coordination between functions the focus of the long term growth. The purpose of research is to know the orientation of market forms of hospital, and to know the performance of hospital based on market oriented. Information obtained can be used as a managerial decision to make changes of organization and as a reference to advanced research , especially in the hospital. The population research is 91 leaders of the hospital , and the withdrawal of the population census conducted .The analysis used cluster is to group of respondents to become homogeneous , as well as manova with the rank of double duncan to test the performance of hospitals performance hospital when dealing with the orientation of the market. The results of the study shown that: ( 1 ) .Focus on customers as much as 9,09 % the hospital , highest emphasis on customers of the other four groups , the focus of a competitor below the average in the group , highest on the performance of occupancy rate , and productivity the lowest in the success of new services.( 2 ) .Focus comprehensive show 36,36 % the hospital , an emphasis on customers , competitors as well as coordination between function , highest performance on the control of the costs of surgery and the performance of the lowest in the success of new services. ( 3 ) .Focus on the function of coordination between , show 22.73 % the hospital , highest emphasis on coordination between a function of the others , the focus of a competitor below the average in the group , highest on the performance of occupancy rate , the performance of the lowest in income growth thorough. ( 4 ) focus does not develop , show 31,82 % the hospital , highest emphasis at the focus of a long period of the four other groups , the focus of a competitor under averages for each group.